Mental health disparities in Latinx immigrant communities residing in the United States during COVID-19: Implications for policy and practice - Pineros-Leano, María; Pérez-Flores, Nancy Jacquelyn; Damian, Katherine; Rodrigues, Kelli; Ortiz, Gabi; Simonovich, Shannon D. (Frontiers in Public Health, 2022)
Objectives Studies have demonstrated that Latinx populations face significant health disparities in access to mental health care. The objective of this study was to describe the impact of the COVID-19 pandemic on the mental health needs of Latinx families, from the perspectives of direct service providers working with Latinx communities. Methods Twenty-one semi-structured interviews were conducted virtually with direct service providers to the Latinx community from August to October 2020. Interviews were transcribed verbatim and analyzed using thematic analysis. Results Two-thirds of providers were female, with a median age of 33 years, and provided direct services to Latinx clients and had extensive experience working with immigrant families, particularly in Massachusetts. Key themes identified describing the impact of COVID-19 on the mental health needs of Latinx families included: (1) exacerbation of mental health symptoms, (2) financial stressors, (3) preoccupation regarding transnational lives, (4) secondary needs becoming more salient, and (5) immigration status as a main driver of inequality. Conclusions Our findings highlight the importance of focusing on the mental health needs of Latinx immigrants and ensuring their access to mental health services. Telehealth seems to be a potential tool that promotes mental health access among Latinx clients. Future research needs to continue investigating the role of telehealth in decreasing mental health access disparities.